Windstorm damage and forest recovery: accelerated succession, stand structure, and spatial pattern over 25 years in two Minnesota forests - Allen, Matthew S.; Thapa, Vaskar; Arévalo, José Ramón; Palmer, Michael W. (Plant ecology, 2012)
We evaluated 25 years of change in windimpacted oak and pine-dominated sites in the Cedar Creek Ecosystem Science Reserve, Minnesota, USA. We address the question: how did the storm alter stand architecture and spatial pattern and how did this affect recovery and recruitment? We mapped and marked all stems greater than 1 cm in diameter in a 0.25 ha oakdominated plot and a 0.30 ha pine-dominated plot. After the initial sampling in 1983, plots were resurveyed four times in the 25 years following the windstorm. We used ordination and diameter distributions to describe compositional and structural characteristics of the sites. The stands are compositionally converging after the windstorm with both moving towards a late-successional forest type dominated by shade-tolerant tree species. The architecture in both sites is similar through time; sites have transitioned from bimodal diameter distributions to reverse-J distributions. We used Ripley's K point pattern analysis to assess spatial patterns of tree mortality and recruitment within each site. In the pine site, surviving trees were significantly clumped, but mortality and recruitment patterns did not significantly differ from random. In the oak site, the storm did not substantially alter the spatial pattern of surviving trees, but subsequent recruitment was significantly associated with trees killed by the storm at scales within 6-8 m and significantly dissociated with surviving trees at scales greater than 1 m. The dynamics of accelerated succession observed here are mediated by the damage and mortality initially sustained and its corresponding effects on spatial patterns of surviving and recruiting trees.